Seroprevalence of Malaria and Hepatitis B Coinfection among Pregnant Women in Tamale Metropolis of Ghana: A Cross-Sectional Study - Gideon Kofi Helegbe; Paul Armah Aryee; Baba Sulemana Mohammed; Anthony Wemakor; David Kolbila; Abdul-Wahid Abubakari; Salam Askanda; Rashid Alhassan; Collins Barnie; Afua Aboagyewaa Donkoh; Ernest Ofosu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Coinfections are becoming common risk factors that may contribute to the increased burden of morbidity in pregnancy. The aim of this study was to assess the seroprevalence of coinfections of malaria, hepatitis B (HBV), human immunodeficiency virus (HIV), and syphilis among pregnant women attending antenatal clinics (ANC) in the Tamale Metropolis. Methods. By means of rapid diagnostic tests (RDTs), pregnant women attending the Tamale Teaching Hospital (TTH) were screened for malaria, HBV infection, HIV infection, and syphilis from March 2013 to February 2015. Haemoglobin (Hb) values, sickling, and glucose-6-phosphate dehydrogenase deficiency (G6PDd) statuses were also assessed using full blood count (FBC), sodium metabisulphite, and methaemoglobin reduction tests, respectively. Logistic regression analysis was performed to estimate the risks/odds ratios (ORs) for the coinfections and other variables (age, gravidity, and time of the first ANC visit) with 95% confidence intervals (CIs) and set p values for accepting any differences at <0.05. Results. Within the two-year study period, data were collected from 3,127 pregnant women. The mean age (SD) of the pregnant women was 28.5 (±5.0) years. Of the total number, seroprevalence was high for malaria (11.6%) and HBV infection (4.2%) and low for HIV infection (1.0%) and syphilis (0.4%) monoinfections. Mal/HBV coinfection was higher (0.7%) when compared with Mal/HIV (0.1%), Mal/syphilis (0.0%), HBV/HIV (0.0%), HBV/syphilis (0.1%), and HIV/syphilis (0.0%) coinfections. The mean Hb (g/dl) for the women with the four monoinfections was significantly different from one another (p=0.009). Pregnant women with malaria infection were about 2 times more likely to be coinfected with HBV even after adjusting for potential confounders (adjusted odds ratio (AOR) = 1.66, 95% CI = 1.04–2.65, p=0.031). Those in their third trimester and visiting the ANC for the first time were significantly less likely to be infected with HBV (AOR = 0.45, 95% CI = 0.28–0.73, p=0.001), with malaria/HBV coinfection (AOR = 0.09, 95% CI = 0.01–0.68, p=0.020), and with any coinfection (AOR = 0.19, 95% CI = 0.06–0.63, p=0.007). Conclusion. A comparatively high seroprevalence of malaria and its coinfection with HBV in pregnant women was observed in this study. Considering the effects that both malaria and HBV have on the liver, it would be expedient to conduct further studies to assess liver function among malaria/HBV-infected individuals, while interventions to prevent coinfections among pregnant women are intensified.